Risk Factors and Outcome of Neonatal Thrombocytopenia - Hira Arif , Nadeem Ikram , Shangraf Riaz , Asma Nafisa, Hira Arif , Nadeem Ikram , Shangraf Riaz , Asma Nafisa (Journal of Rawalpindi Medical College, 2020)
Introduction: About 30% of neonates develop thrombocytopenia during hospital admission. Inevitable and irreversible complications can be prevented by determining the risk factors of neonatal thrombocytopenia. The present study was undertaken to determine the risk factors and outcome of neonatal thrombocytopenia in neonates admitted to Neonatal Intensive Care Unit Benazir Bhutto Hospital Rawalpindi. Materials and Methods: A prospective study was conducted to evaluate the risk factors for neonatal thrombocytopenia (NT) in 160 neonates. Neonatal and maternal risk factors were recorded and neonates were categorized into three groups based on the severity of thrombocytopenia. Results: A higher percentage of the neonates 89 (55.6%) were male. The majority (61.9%) had moderate neonatal thrombocytopenia while 21.9% had severe neonatal thrombocytopenia. A highly significant difference was observed for the distribution of gestational age, platelet count, birth weight, and age at admission (for all p-value ≥0.0001) among different groups. Multivariate logistic regression revealed a significant independent association of prematurity, birth asphyxia, and low birth weight with neonatal thrombocytopenia. Conclusion: Prematurity, low birth weight, and birth asphyxia were the significant causes of Neonatal thrombocytopenia. The mortality rate increased significantly with the severity of thrombocytopenia.